2021
DOI: 10.1016/j.lanwpc.2021.100106
|View full text |Cite
|
Sign up to set email alerts
|

A population-based genomic epidemiological study of the source of tuberculosis infections in an emerging city: Shenzhen, China

Abstract: Background Tuberculosis (TB) in emerging cities is often a disease of recent immigrants, and understanding this epidemiology is crucial for designing effective control and prevention strategies. Methods We conducted a retrospective population-based genomic epidemiological study of culture-positive pulmonary TB patients diagnosed between June 2014 and November 2017 in the Bao'an District of Shenzhen, a Chinese city with dramatic recent growth. After whole genome sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…Internal migrants are thought to play an important role in TB transmission (24)(25)(26). For example, TB in the Baoan District of Shenzhen principally stems from the reactivation of infections acquired by migrants in their home provinces (27). However, our results showed that the clustering rate among local residents was higher than among internal migrants, suggesting that the former played a major role in MDR-TB transmission, especially in the central urban area of Beijing.…”
Section: Discussioncontrasting
confidence: 58%
“…Internal migrants are thought to play an important role in TB transmission (24)(25)(26). For example, TB in the Baoan District of Shenzhen principally stems from the reactivation of infections acquired by migrants in their home provinces (27). However, our results showed that the clustering rate among local residents was higher than among internal migrants, suggesting that the former played a major role in MDR-TB transmission, especially in the central urban area of Beijing.…”
Section: Discussioncontrasting
confidence: 58%
“…Strains were classified into different lineages according to Liu et al [ 12 ]. Strains belonging to lineage 2 (L2), also termed the Beijing family, were divided into L2.3, representing “modern” Beijing and other sub-lineages considered “ancient” Beijing [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Drug-resistance profiles were predicted for 14 anti-TB drugs based on the mutations reported to be associated with resistance [ 14 ], using Whole-genome sequencing (WGS) data as described previously [ 13 ]. Pan-susceptible TB was defined as strains without mutations associated with resistance to the four first-line drugs (isoniazid, rifampicin, ethambutol and pyrazinamide).…”
Section: Methodsmentioning
confidence: 99%
“…Drug-resistance profiles were predicted for 14 anti-TB drugs based on the mutations reported to be associated with resistance, 14 using Whole-genome sequencing (WGS) data as described previously. 15 Pan-susceptible TB was defined as susceptibility to the four first-line drugs (isoniazid, rifampicin, ethambutol and pyrazinamide). Multidrug-resistant TB (MDR-TB) was defined as resistance to at least isoniazid and rifampicin.…”
Section: Methodsmentioning
confidence: 99%